2003
DOI: 10.1021/la026967t
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High Aspect Ratio Poly(ethylene glycol)-Containing Microstructures by UV Embossing

Abstract: The fabrication of high aspect ratio (5 and above) microstructures based upon UV embossing of mixtures containing poly(ethylene glycol) diacrylate (PEGDA) is described. UV embossing is a quick and convenient replication technique using low pressure and room temperature. The biocompatibility and cell- and protein-resistance of PEGDA make deep three-dimensional (3-D) micropatterned PEGDA films potentially useful for many biological applications such as protein delivery, tissue engineering, drug delivery, and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 51 publications
0
88
0
Order By: Relevance
“…To create PEG microstructures, photolithographic methods have been used. [19,23] However, the cost and complexities associated with photolithography provides a barrier to its widespread application for cell and protein patterning. In another approach, polymeric deposition of a PEG-based comb polymer was used to generate topographical changes, but no direct control over feature height was demonstrated.…”
mentioning
confidence: 99%
“…To create PEG microstructures, photolithographic methods have been used. [19,23] However, the cost and complexities associated with photolithography provides a barrier to its widespread application for cell and protein patterning. In another approach, polymeric deposition of a PEG-based comb polymer was used to generate topographical changes, but no direct control over feature height was demonstrated.…”
mentioning
confidence: 99%
“…A direct means of patterning is photolithography [20]. In summary, one can say that photo-cross-linking is a very successful and often applied technique.…”
Section: Patterningmentioning
confidence: 99%
“…Micropatterning of hydrogels has drawn attention as a simple means to direct cell adhesion/growth/function on surfaces, by combining control of surface chemistry and topography. Previous studies have demonstrated the utility of capillary-force lithography/molding under polydimethylsiloxane (PDMS) stamps, [41][42][43][44] molding over microstructured silicon substrates, [45] UV embossing, [46] and photolithographic crosslinking [47][48][49][50] as facile means to create topographically structured PEG hydrogels, including "microwell" microstructures. Because lymphocytes are nonadherent, nonanchorage-dependent cells, [40] we …”
Section: Fabrication Of Hydrogel Microwell Arraysmentioning
confidence: 99%